2021
DOI: 10.3390/su132112081
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Perceptions and Their Characteristics of Middle School Students Regarding the Effectiveness of the “0th Period Physical Education Class” in South Korea: The Q Methodology Application

Abstract: The aim of this study is to explore the subjective perception types and characteristics of Korean middle school students regarding participation in the “0th period physical education class”, a class involving physical movement that takes place before the start of regular school classes in the morning. This goal was achieved by applying the Q methodology, which can categorize the subjective viewpoints of research participants. The selection of the final 25 Q-samples was done by composing the Q-population. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, the Korean education community has yet to implement legal and institutional procedures to settle the "0th-period PE class". For this reason, continuous attention of the academic community should be followed [20]. The results of this study produced academic intellectual assets that could be systematically implemented in a "0th-period PE class" in Korea.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, the Korean education community has yet to implement legal and institutional procedures to settle the "0th-period PE class". For this reason, continuous attention of the academic community should be followed [20]. The results of this study produced academic intellectual assets that could be systematically implemented in a "0th-period PE class" in Korea.…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al [40] suggested that the program not only manages stress but also prevents deviations from school for students. Jeon et al [20] explored Korean middle school students' subjective perception types and characteristics regarding participation in the "0th-period PE class". He concluded that the program was recognized as the driving force for students to maintain a stable school and could be an advantage of the morning exercise program from a parent's point of view.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, physical activity can help prevent depression and enhance psychological well-being and happiness [ 32 ]. Studies on physical education (PE) have explored the relationship between physical activity and mental health, highlighting the psychological benefits of physical activity [ 33 , 34 , 35 , 36 ]. PE classes account for the majority of physical activity during school days and have a positive impact on the physical, mental, and cognitive development of adolescents [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%